Dual-Functional Rainwater Harvesting System - Zaid, Muhammad Naufal; Amdan, Muhamad Azhar; Norafandi, Norakhmal Hafiz; Hamid, Nor Baizura (Multidisciplinary Applied Research and Innovation, 2024)
Water harvesting has become a common practice in modern metropolitan settings. As a result of the paving and building of various metropolitan regions, natural catchment areas have reduced. Not only that, but our country is not immune to the global warming wave, which requires serious consideration. This is demonstrated by the fact that the earth's temperature is rising day by day. The goal of this project is to create innovative, environmentally sustainable building systems. The overall goal of this study is to create a small-scale roof cooling system that produces direct power from rainwater. Additionally, a digital multimeter was used to test the electric current in this dual-purpose rainwater harvesting system, and an environmental meter was used to test the temperature in the cooling system. This experiment aims to demonstrate that the created model functioned well in the tests carried out. The average reading voltage test findings for the first, second, and third readings are 0.020 volts, 0.122 volts, and 0.133 volts, respectively. According to the turbine test results, that is the voltage value, the third reading value is greater than the first and second readings. Based on temperature tests, the average temperatures before and after 10 AM were 31.5 °C and 30.5 °C, respectively. But at noon, the temperature was 34.6 °C and 33.0 °C; the value was decreasing. The average value at 2 PM before was 32.3 °C and 31.3 °C after the system was applied. This temperature value is obtained by using an environmental meter that shows the temperature difference between before and after. The reading value for before and after 12 PM shows a higher temperature difference value of 1.6 °C compared to the difference for 10 PM and 2 PM, which is 1.0 °C.